2012
DOI: 10.1007/s00405-012-2219-9
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and their impact on sinusal extension in chronic rhinosinusitis with nasal polyps

Abstract: 2c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 14 publications
2
32
0
1
Order By: Relevance
“…In a study on tissue samples of CRSwNP and controls, a significantly higher messenger RNA (mRNA) gene expression of MMP-1, MMP-2, and MMP-9 was observed in the CRSwNP group when compared to controls. No significant correlation has been observed between MMP gene expression and sinonasal computed tomography (CT) scan extension [33]. This confirmed a previous report in which MMP-2 and MMP-9 expression intensity was not correlated with the endoscopic or radiological severity of CRSwNP [34].…”
Section: Metalloproteinasessupporting
confidence: 83%
“…In a study on tissue samples of CRSwNP and controls, a significantly higher messenger RNA (mRNA) gene expression of MMP-1, MMP-2, and MMP-9 was observed in the CRSwNP group when compared to controls. No significant correlation has been observed between MMP gene expression and sinonasal computed tomography (CT) scan extension [33]. This confirmed a previous report in which MMP-2 and MMP-9 expression intensity was not correlated with the endoscopic or radiological severity of CRSwNP [34].…”
Section: Metalloproteinasessupporting
confidence: 83%
“…MMP1 cleaves fibrillar collagen, resulting in ECM disruption, and MMP2 and MMP9 degrade type IV collagen, the major structural component of basement membrane. A previous study reported a higher expression of MMP1 mRNA in patients with NPs than in healthy patients, suggesting that MMP1 could play an important role in CRSwNP . Also, several studies have shown that MMP2 and MMP9 values are higher in the CRSwNP and may result in fibrosis of the NPs .…”
Section: Discussionmentioning
confidence: 94%
“…36 However, the MMP-9 expression seems not to be correlated with the severity of nasal polyposis. 37,38 We have previously shown an increased MMP-9 concentration in the UAW of CF patients when compared to controls, and this concentration decreased after intravenous antibiotic therapy. 39 In the present study, if we consider that MMP-9 causes tissue damage and IgA is a protective antibody, 40 the IgA response in the UAW mucosa may counterbalance the MMP-9 production.…”
Section: Discussionmentioning
confidence: 96%